Undergraduate nursing students’ post-coronavirus disease 2019 academic learning experiences at a public university in South Africa: A qualitative study - Wittenschinskey, Claudine H.; ten Ham-Baloyi, Wilma; Kramer, Mercia (Health SA = SA Gesondheid, 2025)
Background: The coronavirus disease 2019 (COVID-19) pandemic disrupted nursing education globally, affecting theoretical instruction, clinical training and students’ well-being. Aim: To explore and describe undergraduate nursing students’ academic learning experiences in the post-COVID-19 period at a South African public university. Setting: A public university in South Africa. Methods: A qualitative, exploratory-descriptive, and contextual design underpinned by Bronfenbrenner’s ecological theory was applied. Twenty-nine purposively selected undergraduate nursing students participated in four face-to-face semi-structured focus group discussions facilitated by an independent fieldworker. Data were thematically analysed by an independent coder. Results: Three themes emerged. Firstly, students reported persistent challenges following the return to in-person learning, including misalignment between teaching and assessment methods, gaps in clinical exposure, and heightened mental health strain. Secondly, enablers of academic success were identified, such as self-directed learning, peer support, and personal and professional development. Thirdly, participants suggested improvements to post-pandemic learning, including curriculum reform, more flexible timetabling, and safer, better-resourced clinical placements. Conclusion: The post-pandemic academic environment continues to shape nursing students’ learning and well-being. While students demonstrated resilience through self-regulation and peer collaboration, institutional reforms remain essential to foster academic success and professional readiness. Contribution: The study provides context-specific insights into post-pandemic nursing education in South Africa and highlights the importance of responsive, student-centred strategies.